Estudio de factibilidad para la creación de una empresa prestadora de servicios de recolección y almacenamiento de residuos peligrosos generados por la industria en la ciudad de Bogotá (2019)
The market research is developed which determines the overall demand-and-bidder overview; To give continuity to the project, a technical study was developed, which established the operative processes to provide the services and the necessary tools to execute them; This part begins the administrative study, which establishes an organizational analysis that leads to a strategic planning of the Company; Now the legal study that determined the instructions in legal material to be able to constitute the company, the environmental study establishes the management of the waste of the process; It is finalized with the financial study where it was determined against the investments, costs, expenses and sales that so viable is the project, this was evaluated with indicators like the present net value (VPN), which results in $615,586,017.48 and the internal rate of Return (TIR) having a value of 115%; Determined that the project is viable and therefore can be realized.